PENGGUNAAN MEDIA KARTU KUATET UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA - Suci Indah Amalia; Asni Deselia Khairunnisa; Nor Hafidah; Aulia Safitri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research was motivated by the low learning outcomes in Pancasila Education among fourth-grade students at SD Negeri Gambut 8, where only 33% of students achieved the minimum mastery criteria due to monotonous learning methods and a lack of interactive media. This Classroom Action Research (CAR) aimed to improve teacher activity, student activity, and learning outcomes by implementing educational quartet card game media across two cycles. The results showed a significant improvement in each cycle; teacher activity increased from 55% at the beginning of Cycle I to 95% (Excellent) at the end of Cycle II, while student activity rose from 61% to 85% (Very Active). This improvement in process quality had a positive impact on classical learning outcomes, which rose drastically from 33% before the intervention to 89% by the end of Cycle II, exceeding the established success indicators. It can be concluded that the use of quartet card media is effective in creating a dynamic and enjoyable learning atmosphere, thereby enhancing conceptual understanding and Pancasila Education learning outcomes for elementary school students.